Pengaruh Ekstrak Biji dan Daun Robusta (Coffea chanophera) dari Desa Kemiri, Jabung-Malang sebagai Penghambat Pertumbuhan Escherichia coli - Zahrotul Millah; Ahmad Syauqi (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Abstract: Coffea chanephora contains secondary metabolites, such as alkaloids, flavonoids, terpenoids, saponins, tannins, and chlorogenic acid an ester group consisting by quinic acid, which functions to protect plants from attack by microorganisms or antibacterial compounds. Significant decrease in antioxidant properties after the drying process caused by the high temperature during the drying process so as to reduce the antioxidant activity of the sample. In accordance with research on the antioxidant resistance test of red kana flower, it was stated that the higher the temperature, the lower the antioxidant activity. The purpose of this study was to determine the growth inhibition of Escherichia coli. This study used an experimental method with “the post-test only control group design” in observing the effectiveness and optimal concentration in inhibiting the growth of Escherichia coli at 45oC. Coffee bean extract added with coffee leaf extract (Coffea chanophera) as an antibacterial on E.coli bacteria had an effect on inhibiting the growth of E.coli with concentrations of 25%, 50%, 75%, and 100% of coffee leaf extract (Coffea chanophera). added with 100% coffee bean extract (Coffea chanophera), all treatments were similar to the positive control but the diameter was smaller and significantly different up to a concentration of 100%.